Pengetahuan dan Perilaku Personal Hygiene Organ Reproduksi Siswi Kelas VIII SMPN 1 Donorojo, Pacitan - Kuswanto Kuswanto (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Background: The results of the preliminary study by interviewing 10 eighth grade female students of Arjosari Pacitan 2 Junior High School were found to be 60% female students with sufficient knowledge because they were able to mention how to care for their reproductive organs, ie washing their genitals from front to back, changing pads 3 times, while 40% less knowledgeable female students because they do not know about how to care for the reproductive organs. In personal hygiene behavior, 70% of students behaved poorly on how to care for their genital organs, and 30% of female students behaved quite well in how to care for their reproductive organs. Methods: This study used a cross sectional design. The study population was students of SMP 1 Donorojo, Pacitan Regency, Class VIII. This study used simple random sampling to obtain 51 students. Data were analyzed using Spearmen Rank test. Results: Based on the results of the research, it was obtained from 51 respondents of class VIII students of SMP N 1 Donorojo, Pacitan Regency, most of the respondents had enough knowledge as much as 24 (47.1%) and a small proportion of respondents had less knowledge as much as 8 (15.7%). And of the 51 respondents of class VIII students of SMP N 1 Donorojo in Pacitan Subdistrict, most of the respondents had fairly good personal hygiene behavior of reproductive organs as many as 35 respondents (68.2%). A small proportion have 5 (9.8%) good behavior. The results showed that there was a relationship between the dependent variable and the dependent variable because the p-value = 0.001. Conclusion: There is a relationship between knowledge about the hygiene behavior of the reproductive organs Keywords: behavior; personal hygiene; reproductive organs; female students ABSTRAK Latar belakang: Hasil studi pendahuluan dengan wawancara kepada 10 siswi kelas VIII SMP Negeri 2 Arjosari Pacitan didapatkan 60% siswi dengan pengetahuan cukup karena mampu menyebutkan bagaimana cara merawat organ reproduksi yaitu sering membasuh alat kelaminnya dari arah depan ke belakang, mengganti pembalut minimal 3 kali, sedangkan 40% siswi berpengetahuan kurang karena tidak tahu tentang cara merawat organ reproduksi. Pada perilaku personal hygiene didapatkan 70% siswi berperilaku kurang baik terhadap cara merawat organ genitalinya, dan 30% siswi diantaranya berperilaku cukup baik terhadap cara merawat organ reproduksinya. Metode: Penelitian ini menggunakan desain cross sectional. Populasi penelitian adalah siswa SMPN 1 Donorojo Kabupaten Pacitan Kelas VIII. Penelitian ini menggunakan teknik simple random sampling sehingga diperoleh 51 siswa. Analisa data yang digunakan adalah uji Spearmen Rank. Hasil: Berdasarkan hasil penelitian didapatkan dari 51 responden siswi kelas VIII SMP N 1 Donorojo Kabupaten Pacitan, sebagian besar responden mempunyai pengetahuan cukup sebanyak 24 (47,1%) dan sebagian kecil responden mempunyai pengetahuan kurang sebanyak 8 (15,7%). Dan dari 51 responden siswi kelas VIII SMP N 1 Donorojo Kecamatan Pacitan, sebagian besar responden mempunyai perilaku personal hygiene organ reproduksi yang cukup baik sebanyak 35 responden (68,2%). Sebagian kecil mempunyai perilaku baik sebanyak 5 (9,8%). Hasil penelitian menunjukkan adanya hubungan variable dependen dengan variable dependen karena nilai p = 0,001. Kesimpulan: Ada hubungan pengetahuan terhadap perilaku kebersihan organ reproduksi Kata kunci: perilaku; personal hygiene; organ reproduksi; siswi